The Impact of COVID-19 on Recent Spanish Emigration Projects: Mobility vs. Immobility - Capote Lama, Alberto; Fernández Suárez, Belén; Vázquez Silva, Iria (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2024)
This article addresses the impact of the COVID-19 pandemic on the migration projects of recent Spanish emigrants in Europe, focusing on France and the United Kingdom. Specifically, we ask how the first months of restrictions on mobility and border controls were experienced, and whether these experiences have left their mark on migration projects. Qualitative interviews were conducted to delve into the experiences and perceptions of the migrants, revealing adaptation strategies and shifts in migration projects. In the short term, the pandemic exacerbated socio-economic and labor inequalities among migrants, while in the medium and long term, there was a reconsideration towards greater stability in both employment and legislative aspects of their destinations. The pandemic underscored the importance of stability and security in destinations, prompting some migrants to seek dual nationality as a guarantee of transnationality. In summary, the pandemic has influenced the perception of mobility and immobility, as well as the pursuit of stability and security in the migration projects of Spaniards in Europe.